ผลของโปรแกรมการจัดการกับอาการร่วมกับสุวคนธบำบัด ต่อภาวะซึมเศร้าของผู้สูงอายุโรคไตวายระยะสุดท้าย ที่ได้รับการฟอกเลือดด้วยเครื่องไตเทียม - รัตนาภรณ์ กรุณา (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This two group pretest and posttest quasi-experimental research aimed to study the effect of symptom management and aromatherapy program on depression among older persons with end stage renal disease received hemodialysis. The samples were 40 older persons diagnosed end stage renal disease and received hemodialysis at Chiangrai Prachanukroh Hospital. They were divided into experimental group and control group equally. The control group received conventional nursing care whereas the experimental group received a symptom management and aromatherapy program which were developed by the researcher based on the Symptom Management Concept with Complementary Concept. The program was conducted individually on the experiment group. The data collecting in this study included 1) The Demographic Data Interview 2) Depression Questionnaire the reliability were .85. Frequency, percentage, mean and standard deviation were used for data analysis, and t-test. The results revealed that 1. The mean score of depression on experimental group after receiving symptom management with aromatherapy program was significantly lower than that of before receiving symptom management and aromatherapy program (p < .05) 2. The mean score of depression on experimental group was significantly lower than that the control group (p < .05).